Echocardiography and extravascular lung water during 3 weeks of exposure to high altitude in otherwise healthy asthmatics - Saxer, S.; Bader, P. R.; Schneider, S. R.; Mademilov, M.; Sheraliev, U.; Appenzeller, P.; Müller, J.; Sooronbaev, T. M.; Bloch, K. E.; Ulrich, S.; Lichtblau, M. (Frontiers in Physiology, 2023)
This prospective, observational study showed for the first time the acute and subacute effects of exposure to the hypobaric hypoxic environment on right heart function, including pulmonary artery pressure (PAP), and extravascular lung water (EVLW) in patients with mostly mild asthma who participate in a three-week asthma rehabilitation program at altitude (3100m). Very little is known about the acclimatization in asthmatics but otherwise healthy middle-aged lowlanders travelling to and staying at high altitude. We could show that in accordance with healthy, PAP rapidly increases with acute exposure to altitude, albeit remaining below a level that would define pulmonary hypertension along with an increased pulmonary vascular resistance (PVR). These changes went along with the expected decrease in oxygen saturation and increase in heart rate at altitude. EVLW assessed as Blines increased upon acute exposure to high altitude but returned to baseline values after three weeks.